PENGARUH TIME BUDGET PRESSURE, KOMPLEKSITASTUGAS, DAN KOMPETENSI TERHADAP KUALITAS AUDITDENGAN SUPERVISI AUDIT SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perwakilan BPKP Provinsi Sumatera Selatan) - Oloan Siagian; Inten Meutia (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2016)
This study aims to examine the effect of time budget pressure, task complexity, and competence on audit quality at BPKP Representatives of South Sumatra Province with audit supervision as a moderating variable.Data collection is done using a questionnaire. The number of samples in this study were 100 auditors and were selected based on the census method. The analysis technique used is multiple linear regression and residual test.The results showed that the time budget pressure had a negative effect on audit quality, but it did not have a significant effect on audit quality, task complexity had a significant negative effect on audit quality, while competence had a significant positive effect on audit quality. The audit supervision variable is a variable that moderates the effect of time budget pressure on audit quality, while the audit supervision variable is not a variable that moderates the effect of task complexity on audit quality, as well as the audit supervision variable is not a variable that moderates the influence of competence on audit quality.This study has several limitations that can be used as a direction for future research. Future research can be done by including variables related to auditor morality and auditor motivation.